The The Analysis of Symbolism Related to Ecocriticism Found In Movie “Man” by Steve Cutts - Komang, Ni Komang Trisya Suasti (Journal of Humanities, Social Science, Public Administration and Management (HUSOCPUMENT), 2024)
This comprehensive study endeavors to delve deeply into the intricate relationship between eco-criticism and symbolism within the captivating realm of the illustrated film "Man" by Steve Cutts. The primary objective is to illuminate and elucidate the intended messages the creators seek to impart, thereby facilitating a nuanced understanding for the audience. Through meticulous analysis, this research unearths three distinct facets of symbolism prevalent within the film: the utilization of colors, the portrayal of characters, and the significance of objects. Within this exploratory framework, it becomes evident that Cutts' visual narrative deftly encapsulates profound reflections on the intricate dynamics between humanity and the natural world. Through the strategic implementation of color schemes, the portrayal of protagonist behavior, and the symbolism embedded within various objects, the film conveys poignant messages regarding humanity's relationship with the environment and its inhabitants. Thus, this study serves to not only dissect the symbiotic interplay between eco-criticism and symbolism but also to underscore the film's profound thematic resonance and its potential impact on audience perception and consciousness.